2024
DOI: 10.1002/anie.202319755
|View full text |Cite
|
Sign up to set email alerts
|

Dithienoquinoxalineimide‐Based Polymer Donor Enables All‐Polymer Solar Cells Over 19 % Efficiency

Zongtao Wang,
Xin Wang,
Lijun Tu
et al.

Abstract: All‐polymer solar cells (all‐PSCs) have been regarded as one of the most promising candidates for commercial applications owing to their outstanding advantages such as mechanical flexibility, light weight and stable film morphology. However, compared to large amount of new‐emerging excellent polymer acceptors, the development of high‐performance polymer donor lags behind. Herein, a new D‐π‐A type polymer donor, namely QQ1, was developed based on dithienoquinoxalineimide (DTQI) as the A unit, benzodithiophene w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…1–3 In recent years, owing to the development of fused ring electron acceptors (FREAs), especially the ITIC-series with an acceptor–donor–acceptor (A–D–A) structure and Y-series with an A–DA′D–A structure, the power conversion efficiencies (PCEs) of single-junction OSCs have exceeded 19%. 4–21 However, the large rigid ladder-type fused ring cores in these efficient FREAs generally require multiple-step synthesis and purification, resulting in high synthetic costs of acceptors, which has been considered as one of the major obstacles to large-scale production. Nonfused electron acceptors have emerged as potential alternatives for achieving cost-effective OSCs due to their concise synthesis, high stability and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…1–3 In recent years, owing to the development of fused ring electron acceptors (FREAs), especially the ITIC-series with an acceptor–donor–acceptor (A–D–A) structure and Y-series with an A–DA′D–A structure, the power conversion efficiencies (PCEs) of single-junction OSCs have exceeded 19%. 4–21 However, the large rigid ladder-type fused ring cores in these efficient FREAs generally require multiple-step synthesis and purification, resulting in high synthetic costs of acceptors, which has been considered as one of the major obstacles to large-scale production. Nonfused electron acceptors have emerged as potential alternatives for achieving cost-effective OSCs due to their concise synthesis, high stability and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…1–8 In the past few years, the meteoric development of active layer materials, interface engineering, and morphology modulation of the active layer have led to significant progress in the power conversion efficiency (PCE) of polymer solar cells (PSCs), which has surpassed 19%. 9–14 Furthermore, all-polymer solar cells (all-PSCs), as a typical prototype of OSCs, have also been progressing rapidly, 15–22 with some demonstrating PCEs greater than 18%. 18–22 For instance, Peng et al demonstrated the fabrication of all-polymer solar cells (PSCs) using a polymer donor PBBTz-Cl and two polymer acceptors PYIT and BTP-2T2F, achieving an impressive PCE of 18.60%.…”
Section: Introductionmentioning
confidence: 99%
“…Organic solar cells (OSCs) are an encouraging photovoltaic technology with lightweight, low-cost, and mechanical flexibility advantages. Recently, with the progress of device engineering and innovation of active layer materials, the power conversion efficiencies (PCEs) of polymer-based OSCs (P-OSCs) have been continuously broken through, surpassing 20%. Compared with P-OSCs, all-small-molecule OSCs (ASM-OSCs) have advantages of well-defined molecule structure and low variations between batches, etc. Unfortunately, the PCEs of ASM-OSCs are relatively inferior mainly imputed to the unmanageable molecule aggregation and phase separation behaviors in the active layers. Therefore, it is of great significance to fine-tune active layer morphologies to realize efficient charge transport and extraction, thus improving the PCEs of ASM-OSCs.…”
mentioning
confidence: 99%